Implementation and Use of Risk Evaluation and Mitigation Strategies Programs in Practice: A Scoping Review of the Literature - Tajchman, Sharla; Lawler, Brooke; Spence, Nathan; Haque, Saira; Quintana, Yuri; Ateya, Mohammad (Applied Clinical Informatics, 2022)
Background Risk Evaluation and Mitigation Strategy (REMS) programs intend to improve medication safety but can add significant administrative burdens to providers and health systems. Various stakeholders have made efforts to use technology to improve REMS programs.Objectives The objective of this scoping review is to describe studies evaluating workflows, automation, or electronic data exchange related to REMS programs.Methods A literature search of PubMed, Embase, and Web of Science was performed for articles published between January 2007 and July 2021. Studies were identified using the relevant Medical Subject Headings terms and related keywords. Articles must have described a workflow change and measured the impact of the workflow change.Results Of 299 citations initially identified, 7 were included in the final review after removing duplicates and articles not meeting predefined inclusion criteria. Included studies consisted of three manuscripts and four conference abstracts. Electronic health record interventions, such as customized order sets and clinical decision support alerts, were the most common strategy reported. Other strategies included developing a portal to verify REMS enrollment, requiring prescribers to contact the dispensing pharmacy, provider education, and restrictions based on the provider specialty. One study evaluated automated data exchange for REMS program processes in a mock environment. Although only three studies reported baseline metrics for comparison, all studies noted an improvement or benefit to the implemented workflow process changes.Conclusion There is limited evidence describing REMS workflows, automation, and electronic data exchange. Various strategies to address REMS program requirements were reported, but no studies described the use of data exchange standards in a real-world setting despite efforts by the Food and Drug Administration and other stakeholders. Additional efforts are needed to automate REMS programs.
Keywords: risk evaluation and mitigation; health information interoperability; workflow; REMS; patient safety